Editorial Vol.7(3) (Bangladesh Journal of Bioethics, 2016)
Philosophers and ethicists have long neglected moral questions that arise from our interaction with non-human animals. Most assumed that human beings have a higher moral status than other animals, and that it is therefore morally permissible to use non-human animals as a source of food, clothing, and entertainment, and for scientific purposes. In recent decades, however, that assumption has been challenged, and the moral status of non-human animals is now the subject of a lively and controversial academic debate.Advances in sciences, particularly the advent of evolutionary theory, made us realize that human beings and other animals are more similar than different, and force us to rethink our place in nature. We are no longer justified in thinking of ourselves as the crown of creation. We now understand that we are just one species among others, and we must ask ourselves anew with an open and critical mind and without bias which values and principles should guide our interaction with non-human animals, and how we should weigh our interests against those of other animals.Recognizing this important trend in moral thinking, the Bangladesh Journal of Bioethics invited me to edit a special issue on animal ethics. The interest was so great that one issue became two, of which this is the first. I am grateful to Professor Shamima Parvin Lasker and Ms. Tahera Ahmed for giving me the opportunity to serve as a guest editor, and for their assistance during the editing process. I also thank our contributors for choosing this journal to publish their excellent work, and the reviewers for their insightful comments and suggestions.This, the first special issue on animal ethics contains the following five articles:Robin Attfield and Rebekah Humphreys (Justice and Non-Human Animals) challenge the widely held belief that non-human animals are not included within the scope of the principles of justice, and suggest that the interests of non-human animals sometimes take precedence over the interests of human beings. The implications of their argument for our interaction with other animals are profound: E.g., it is a matter of justice and fairness to prevent avoidable and unnecessary animal suffering, rather than a mere matter of compassion.Eric X. Qi (Special Relations, Special Obligations, and Speciesism) develops an account of the moral significance of special relations, and uses it to argue for a modest form of speciesism that steers a middle ground between anti-speciesism and crude speciesism. Unlike anti-speciesists, he maintains that species co-membership grounds special moral obligations among the members of the same species. In contrast to crude speciesists, however, he holds that our special obligations to fellow human beings do not warrant that we always attach more weight to their interests than to the comparable interests of non-human animals.Yamikani Ndasaukaand Grivas M. Kayange (Existence and Needs: A case for the equal moral considerability of non-human animals) argue that the existentialist view that human beings have a higher moral status than other animals rests on a weak foundation. They consider a number of arguments that have been made in support of this view and conclude that none of them holds up to critical scrutiny. They then suggest that human beings and other animals in fact deserve equal moral consideration, and drawing from Martin Heidegger and Abraham Maslow ground that claim in two important commonalities between them.Sreetama Chakraborty (Animal Ethics: Beyond Neutrality, Universality, and Consistency) explains how the postmodern approach to animal ethics departs from the traditional approach, particularly its emphasis on the principles of neutrality, universality, and consistency, and draws attention to the pernicious hierarchy of domination that separates human beings from other animals. Building on the insights of postmodernism, she takes first steps towards a new, non-anthropocentric paradigm, in the hope to achieve a sustainable balance between human interests and the interests of non-human animals.Gabriel Vidal Quiñones (Singerian Vegetarianism and the Limits of Utilitarianism: A path towards a Meaning Ethics) takes a critical look at Peter Singers utilitarian argument for vegetarianism, and argues that the conceptual resources of utilitarianism only allow for an incomplete moral understanding of our relationship with other animals. What is lacking, he suggests, is an ethical vision. He argues that, without an ethical vision, human action threatens to degenerate into mere automatism without meaning. He proposes a meaning ethics that he thinks is better equipped to help us decide how we ought to treat other animals.I hope you, dear reader, will enjoy reading through this remarkable collection of articles as much as I enjoyed putting it together. Maybe you will even be inspired to do some thinking of your own about issues of animal ethics and put your thoughts down on paper. If so, I sincerely hope that you will choose the Bangladesh Journal of Bioethics to publish your article.Warm regards and best wishes for the new year,